2016
DOI: 10.3788/col201614.081404
|View full text |Cite
|
Sign up to set email alerts
|

PMMA-doped CdSe quantum dots as saturable absorber in a Q-switched all-fiber laser

Abstract: We demonstrate the generation of Q-switched pulses from an ytterbium-doped fiber laser (YDFL) using quantum dot (QD) CdSe as a passive saturable absorber (SA). The CdSe QD is fabricated by the synthesis of CdO, Se, and manganese acetate and paraffin oil and oleic acid as the solvent and surfactant, respectively. The CdSe QD is then doped into poly-methyl-methacrylate (PMMA) via an emulsion polymerization process. A PMMAhosted CdSe QD thin flake with a homogeneous end surface is then formed and placed between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 38 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…More recently, quantum dot (QD) semiconductor crystal, the 0D material was also joining the group of nanocluster materials for various applications including SA, [13] synthesis of the solar cell, [14] as energy filtered electron microscopy [15] and also for biological application. [16] It was also reported that QDs grown on a semiconductor substrate could emit laser in the wavelength range of 1.0 µm-1.9 µm.…”
mentioning
confidence: 99%
“…More recently, quantum dot (QD) semiconductor crystal, the 0D material was also joining the group of nanocluster materials for various applications including SA, [13] synthesis of the solar cell, [14] as energy filtered electron microscopy [15] and also for biological application. [16] It was also reported that QDs grown on a semiconductor substrate could emit laser in the wavelength range of 1.0 µm-1.9 µm.…”
mentioning
confidence: 99%
“…Using thermal free-radical polymerization, pure PMMA and PMMA/admixture were produced. Benzoyl peroxide (for synthesis, SIGMA-ALDRICH, Germany) was used as the initiator, and thioglycolic acid TGA (98%, Aldrich) was used as the chain transfer agent [ 39 , 40 , 41 ]. CdSe quantum dots obtained earlier were added to the polymerization mixture, which also contained methyl methacrylate and polymerized.…”
Section: Resultsmentioning
confidence: 99%
“…Such quantum dot-doped polymer matrices were deposited on LEDs to study the effects of different weight ratios of CdSe QDs and PMMA on the performance of white LEDs. Other teams of researchers [ 40 , 41 , 42 , 43 , 44 , 45 , 46 ] have also been involved in creating composites and structures combining polymers with quantum dots. These were mainly films and thin films with the addition of different types of quantum dots, depending on further applications.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, there have been many new attempts in recent years to develop new high-performance SAs for Q-switching laser operation. [8,9] Despite many methods and new materials being explored in developing the SA for Q-switching pulse generation, metal nanoparticles-based SA, especially transition metal elements, are rarely being investigated. Transition metal oxides such as zinc oxide (ZnO), titanium dioxide (TiO 2 ) and cobalt oxide (Co 3 O 4 ) are another class of nonlinear optical materials that have been intensively investigated over the past few decades due to their large optical nonlinearity and the advantages of good thermal and chemical stability in addition to mechanical strength.…”
mentioning
confidence: 99%